Extractive Desulphurization on Model Oil using 1-Butyl-3-Methylimidazolium Tricyanomethane - Syamsul, Abdullah; Z., Man (2016)

(untitled)
In this study, experiments were conducted for the removal of sulfur compound (present as benzothiophene or BT) with concentration of 2000 ppm in the model oil (present as n-dodecane or nC12) using 1-butyl-3-methylimidazolium tricyanomethane ([bmim][TCM]) as the extractant. The effects of stirring speed, extraction time and water content on the extraction efficiency were investigated. In the end, the loading factor of the [bmim][TCM] is also discussed.